Nov pogled na spomenike v pokrajini Črnega pasu - Giliberti, Marco (Urbani izziv, 2013)
Although many old sites are well preserved, many sites of historical and cultural value in the United States are disappearing due to their abandonment.In some cases, the condition of these sites makes restorers' work very difficult. In other cases, in order to recover blighted local economies, administrations and cultural institutions are adopting strategic spatial plans to attract tourists or accommodate historical theme parks. However, recent scholarly interest in the interaction of history and collective memory has highlighted these sites. Even if the memory of some historical sites is fading quickly, this memory is receiving greater attention than in the past inorder to enhance local identity and strengthen the sense of community. This article examines a number of plans and strategies adopted to give shape to the memorial landscape in Alabama, thereby documenting and exploring some key relations between city planning and the commemoration of African-American history.
Keywords: Afroameričani; Alabama; črnci; kulturna identiteta; prostorsko planiranje; regionalna identiteta; spatial planning; spomeniško varstvo; United States of America; ZDA; Združene države Amerike